ANALISIS PENGUKURAN KINERJA KOPERASI SYARIAH BERDASARKAN BALANCED SCORECARD (STUDI PADA KOPERASI SYARIAH BAITURRAHMAN BANDA ACEH) - Hanif Syah Reza Funna; Suazhari Suazhari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to determine the performance of Baiturrahman Sharia Cooperative based on the balanced scorecard method. This research is descriptive with the method of collecting data documentation, interviews, and questionnaires. The analysis used is the Balanced Scorecard analysis. The respondents in this study were 93 cooperative members and 14 cooperative employees. Based on the results of the study using the balanced scorecard, the financial perspective obtained values in each ratio, namely the current ratio of 25, Total Debt to Total Asset Ratio of 0, and Return On Asset of 25 which showed poor performance in the cooperative financial perspective. In the customer perspective, customer retention has increased by 24%, the level of customer acquisition has increased by 10%, as well as the level of customer satisfaction which has a score of 4.0 which shows good customer performance. In the perspective of internal business processes, the innovation process gets a score of 4.6, the operating process gets a score of 4.7, and good after-sales service shows the performance of a good internal business process perspective. In the perspective of learning and growth, employee productivity increases, the results of employee retention indicate that the company can hold employees accountable, and employee satisfaction which scores 4.6 which shows performance in the perspective of good cooperative learning and growth. Overall, the four perspectives show good categories except in a financial perspective.